Khaliq Qureshi, Person and Poet: An Overview - Hameed Khan, Shaista; Mushtaq, Majid; Hussain, Matloob (sourcecoder, 2022)
Khaliq Qureshi was a great Journalist and poet of twentieth century. He had a personality of different aspects; a journalist, poet, political worker, editor and social worker. After his death some critical work printed in newspapers but their effort is not sufficient for his literary contributions. This article is a path to know his literary dimensions as well as his personality. So, this article may lead the new scholars towards Khaliq Qureshi’s literary work.